Solutions of Islamic Lesson Learning in Interest Problem by Using Variety of Teaching Style - Sri Herlina (AT-TURATS, 2021)
This  study  is  based  on  indications  that  the  level  of  interest  in  learning  students  towards  Islamic Religious Education (PAI) subjects is still low before getting action. Then after it is known that the low interest  in  learning,  then  researchers  offer  solutions  with  the  concept  of  Teaching  Style Variations. Researchers use Class Action Research (PTK) with quantitative approach. As for the data  collection techniques  in  this  study,  researchers  used  three  techniques,  namely  observation,  questionnaire  and docume ntation.  Observations  used  by  researchers  are  observation  sheets  related  to  Variations  in Teaching  Style.  Based  on  the  results  of  the  data  analysis,  it  can  be  concluded  that,  The  Interest  of Learning  Grade  II  Students  in  Islamic  Religious  Education  Subjects  (PAI)  before  getting  action (Through Variations in Teaching Style) is still low, which is 29.75%. But once they get a Variety of Teaching Styles or actions in the first cycle the student's interest level gets better, even the change in the student's  increases cyclically, which is 60.25%. Or their interest  increase by 30.5%. This shows that with the implementation of Teaching Style Variations are useful to increase the interest in learning.